2018
DOI: 10.1371/journal.pone.0203932
|View full text |Cite
|
Sign up to set email alerts
|

Changes in human intervertebral disc biochemical composition and bony end plates between middle and old age

Abstract: ObjectiveThis study evaluates molecular, nutritional and biochemical alterations in human intervertebral discs between middle and old age.MethodsTwenty-eight human lumbar intervertebral discs from donors were evaluated and separated into two groups: Middle-aged (35–50 years old, relatively non-degenerate discs of Pfirrmann grades 1–3, n = 15) and Old-aged (≥80 years old, all degenerate Pfirrmann grade 4 or 5, n = 13). Parameters which might be expected to to be related to nutrient supply and so the health of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 50 publications
2
22
0
1
Order By: Relevance
“…The initial candidate materials chosen for assessment with our in vitro disc innervation model were chondroitin sulfate (CS) biomaterials as there is a robust connection between increased disc innervation and the reduction of neuroinhibitory CSPGs that occurs with age and disc degeneration . The neuroinhibitory properties of CSPGs are determined by the different sulfation patterns of the CS the CSPGs contain because the sulfation pattern determines the neuronal receptors to which the CS can bind .…”
mentioning
confidence: 99%
“…The initial candidate materials chosen for assessment with our in vitro disc innervation model were chondroitin sulfate (CS) biomaterials as there is a robust connection between increased disc innervation and the reduction of neuroinhibitory CSPGs that occurs with age and disc degeneration . The neuroinhibitory properties of CSPGs are determined by the different sulfation patterns of the CS the CSPGs contain because the sulfation pattern determines the neuronal receptors to which the CS can bind .…”
mentioning
confidence: 99%
“…The thickness of the bony endplate is greatest in the lumbar vertebra, with the anterior shell thickness greater than the posterior in both endplates, cranial and caudal to the disc (Edwards et al, 2001). The bony endplate is thinnest and most porous in the central region of the vertebra adjacent to the NP (Edwards et al, 2001;Zehra et al, 2015) The caudal bony endplate has significantly more marrow contact pores than the cranial endplate (Martins et al, 2018).…”
Section: Vertebral Bodies and Bony Endplatementioning
confidence: 99%
“…Further work is needed on facet joints, investigating alternate loading modalities, magnitudes and frequencies, as well as assaying additional anabolic outputs. In skeletal muscle, exercise is known to increase collagen synthesis rates and have broad anti-inflammatory effects (Miller et al, 2005;Petersen and Pedersen, 2005). Work in the SPARC null mouse model, which exhibits spontaneous disc degeneration, demonstrated that fibrotic remodelling and inflammation of the multifidus muscle could be successfully attenuated with physical activity (James et al, 2018;James et al, 2019).…”
Section: Cell-free Approaches: Physical Therapy and Anabolic Loadingmentioning
confidence: 99%
“…Two distinct regions in intervertebral discs can be characterize, i.e ., annulus fibrosus (AF) with high amounts of collagen and nucleus pulposus rich in proteoglycans. ( 1 ) The principal proteoglycans found in intervertebral discs are aggrecan noncovalently attached to hyaluronic acid (HA). These proteoglycans' function allows compressive loads to intervertebral discs.…”
Section: Introductionmentioning
confidence: 99%
“…Há possibilidade de caracterização de duas regiões distintas nos discos intervertebrais: anel fibroso, com altas quantidades de colágeno, e núcleo pulposo (NP), rico em proteoglicanos. ( 1 ) Os principais proteoglicanos encontrados nos discos intervertebrais são agrecan aderidos de forma não covalente ao ácido hialurônico (AH). Sua função é permitir cargas compressivas nos discos intervertebrais.…”
Section: Introductionunclassified